Authorization as the Problem of the Choice of Case: System of Russian Syntax and the Problems of Teaching RFL (Proceedings of Southern Federal University. Philology, 2020)
One of the critical and difficult moments in the development of the Russian language by foreigners is the transfer of subjective meanings. The existing terminological and methodological difficulties in studying this issue do not remove the need to teach in the course of Russian language for foreigners means of expressing subjective meanings. The problem is aggravated by the discrepancies between the description of these means in the grammars of the Russian language, including the academic one and the actual functioning. This is most clearly manifested in the functioning of variable prepositional-case forms (for example, вслед чему-либо, кому-либо – вслед зачем-либо, кем-либо, where only the second form can be used in the function of the authorizer: вслед за академиком Виноградовым). The particular difficulty for foreigners is also deanonymization prepositionalcase forms, the paradigm of values which includes the authorization, such as у кого-либо, для кого-либо, and the like. As a result, the elaboration of a system of rules of use and a system of exercises for training the use of means of expression of subjective meanings requires not only methodological but also theoretical justification. We offer such a justification in the form of systematization of these means based on the concept of «authorization» as used in the functional-communicative grammar of G. A. Zolotova, and a typology of syntaxes made in the same concept (free, structurally-driven, connected). The developed system of rules and exercises is implemented in a textbook for Iranian advanced students and tested in teaching in higher educational institutions of Iran. It includes the development of syntagmatic and paradigmatic of substantive and verbal authorization means, differentiation of syntactic synonymy and limitation of syntactic homonymy, considering stylistic parameters. The rules provide the maximum approximation to the living modern use of substantive and verbal authorization means in compliance with the methodological principles of compactness and consistency of the formulation. The exercises require the development of authorization tools in context, so that students confidently include them in any sentence structure. The interrelated development of form, meaning and function corresponds to the trilateral essence of the language sign, which makes the proposed model of training not only methodically effective, but also theoretically solid and modern.Keywords: modality, subjective values, authorization, functional communicative approach, syntaxeme.DOI 10.18522/1995-0640-2020-1-198-206